Correlation Between Basal Metabolic Rate and Clinical Outcomes in Gastric Cancer Patients: A Retrospective Study - Yun-Shi Huang; Xiu-Ya Zeng; Wei-Sheng Chen; Wen-Tao Cai (Journal of Investigative Surgery)
Objectives Hypermetabolism is associated with clinical prognosis of cancer patients. The aim of this study was to explore the association between basal metabolic rate (BMR) and postoperative clinical outcomes in gastric cancer patients.Methods We collected data of 958 gastric cancer patients admitted at our center from June 2014 to December 2018. The optimal cutoff value of BMR (BMR ≤1149 kcal/day) was obtained using the X-tile plot. Logistic and Cox regression analyses were then performed to evaluate the relevant influencing factors of clinical outcomes. Finally, R software was utilized to construct the nomogram.Results A total of 213 patients were defined as having a lower basal metabolic rate (LBMR). Univariate and multivariate analyses showed that gastric cancer patients with LBMR were more prone to postoperative complications and had poor long-term overall survival (OS). The established nomogram had good predictive power to assess the risk of OS in gastric cancer patients after radical gastrectomy (c-index was 0.764).Conclusions Overall, LBMR on admission is associated with the occurrence of postoperative complications in gastric cancer patients, and this population has a poorer long-term survival. Therefore, there should be more focus on the perioperative management of patients with this risk factor before surgery.